GENDER DISCRIMINATION IN KATE CHOPIN’S FIVE SHORT STORIES - Uci Nurhidayati Rosita; Wilujeng Asih Purwani (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2022)
Abstract This study aims to describe the forms of gender discrimination in the marriage system experienced by the main female character and the forms of resistance of the main female character against oppression. The author chose five short stories of Kate Chopin to study, namely The Story of An Hour, A Respectable Women, Desire’s Baby, The Storm, A Pair of Silk Stockings.The research method used is a qualitative descriptive method with a feminist literary criticism approach. Based on the results of data analysis, it is produced as follows. 1) The forms of discrimination experienced by the main women in the story 2) The form of resistance against oppression by the main female character in the story. The references used feminist journals, especially liberal feminism from naomi wolf theory which includes the theory of power feminism. Keywords: discrimination, Kate Chopin, short stories Abstrak Penelitian ini bertujuan untuk mendeskripsikan bentuk bentuk diskriminasi gender dalam sistem perkawinan yang dialami tokoh perempuan utama dan bentuk perlawanan tokoh perempuan utama dalam melawan penindasan.Penulis memilih lima cerita pendek kate chopin untuk diteliti yaitu The story of an hour, A respectable women, Desire baby, The storm, A pair of silk stockings.Metode penelitian yang digunakan adalah metode deskriptif bentuk kualitatif dengan pendekatan kritik sastra feminis. Berdasarkan hasil dari analisis data, maka dihasilkan sebagai berikut. 1) Bentuk bentuk diskriminasi yang di alami perempuan utama dalam cerita. 2) Bentuk perlawanan melawan penindasan yang di lakukan tokoh perempuan utama dalam cerita. Referensi yang digunakan adalah referensi dari jurnal jurnal feminisme khususnya feminisme liberal dan teori naomi wolf yang mencakup teori feminisme kekuatan dari salah satu macam bentuk feminisme liberal yang digagas oleh naomi wolf sebagai tinjauan dalam analisa Kata kunci: diskriminasi, Kate Chopin, cerita pendek